A geometry problem by Skanda Prasad

Geometry Level 3

Given that in a triangle A B C ABC with side lengths a a , b b and c c ,

cot A 2 cot B 2 = c cot B 2 cot C 2 = a cot C 2 cot A 2 = b \begin{aligned} \cot\dfrac{A}{2} \cot\dfrac{B}{2} & =c \\ \cot\dfrac{B}{2} \cot\dfrac{C}{2} & =a \\ \cot\dfrac{C}{2} \cot\dfrac{A}{2}& =b \end{aligned}

Find the value of 1 s a + 1 s b + 1 s c \dfrac{1}{s-a}+\dfrac{1}{s-b}+\dfrac{1}{s-c} , where s = a + b + c 2 s=\dfrac{a+b+c}{2} .


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Sep 22, 2016

Using sine rule , we have:

c sin C = a sin A = b sin B cot A 2 cot B 2 sin C = cot B 2 cot C 2 sin A = cot C 2 cot A 2 sin B 1 tan A 2 tan B 2 2 tan C 2 1 + tan 2 C 2 = 1 tan B 2 tan C 2 2 tan A 2 1 + tan 2 A 2 = 1 tan C 2 tan A 2 2 tan B 2 1 + tan 2 B 2 1 + tan 2 C 2 2 tan A 2 tan B 2 tan C 2 = 1 + tan 2 A 2 2 tan A 2 tan B 2 tan C 2 = 1 + tan 2 B 2 2 tan A 2 tan B 2 tan C 2 1 + tan 2 C 2 = 1 + tan 2 A 2 = 1 + tan 2 B 2 C = A = B = 6 0 \begin{aligned} \frac c{\sin C} & = \frac a{\sin A} = \frac b{\sin B} \\ \implies \frac {\cot \frac A2 \cot \frac B2}{\sin C} & = \frac {\cot \frac B2 \cot \frac C2}{\sin A} = \frac {\cot \frac C2 \cot \frac A2}{\sin B} \\ \frac {\frac 1{\tan \frac A2 \tan \frac B2}}{\frac {2\tan \frac C2}{1+\tan^2 \frac C2}} & = \frac {\frac 1{\tan \frac B2 \tan \frac C2}}{\frac {2\tan \frac A2}{1+\tan^2 \frac A2}} = \frac {\frac 1{\tan \frac C2 \tan \frac A2}}{\frac {2\tan \frac B2}{1+\tan^2 \frac B2}} \\ \frac {1+\tan^2 \frac C2}{2\tan \frac A2 \tan \frac B2 \tan \frac C2} & = \frac {1+\tan^2 \frac A2}{2\tan \frac A2 \tan \frac B2 \tan \frac C2} = \frac {1+\tan^2 \frac B2}{2\tan \frac A2 \tan \frac B2 \tan \frac C2} \\ \implies 1 + \tan^2 \frac C2 & = 1 + \tan^2 \frac A2 = 1 + \tan^2 \frac B2 \\ \implies C & = A = B = 60^\circ \end{aligned}

a = b = c = cot 2 3 0 = 3 s = 9 2 \implies a=b=c = \cot^2 30^\circ = 3 \implies s = \dfrac 92

1 s a + 1 s b + 1 s c = 3 9 2 3 = 2 \implies \dfrac 1{s-a} + \dfrac 1{s-b} + \dfrac 1{s-c} = \dfrac 3{\frac 92 - 3} = \boxed{2}

Woah, awesome!!!

ADAMS AYOADE - 4 years, 8 months ago
Ahmad Saad
Nov 2, 2016

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...